2009
DOI: 10.1111/j.1365-294x.2009.04284.x
|View full text |Cite
|
Sign up to set email alerts
|

Reverse sex‐biased philopatry in a cooperative bird: genetic consequences and a social cause

Abstract: The genetic structure of a group or population of organisms can profoundly influence the potential for inbreeding and, through this, can affect both dispersal strategies and mating systems. We used estimates of genetic relatedness as well as likelihood-based methods to reconstruct social group composition and examine sex biases in dispersal in a Costa Rican population of white-throated magpie-jays (Calocitta formosa, Swainson 1827), one of the few birds suggested to have female-biased natal philopatry. We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 65 publications
1
45
0
1
Order By: Relevance
“…It is difficult to explain the absence of sex‐biased dispersal in grey‐crowned babblers when the phenomenon is so widespread among otherwise similar cooperatively breeding birds. The forces driving sex‐biased dispersal in cooperative birds and mammals are poorly understood (Berg et al. 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to explain the absence of sex‐biased dispersal in grey‐crowned babblers when the phenomenon is so widespread among otherwise similar cooperatively breeding birds. The forces driving sex‐biased dispersal in cooperative birds and mammals are poorly understood (Berg et al. 2009).…”
Section: Discussionmentioning
confidence: 99%
“…We do not view the assumption that individuals in leader-follower relationships are related as restrictive because genetic relatedness has been shown to help facilitate the emergence of many types of social interactions and social organisations (McElreath and Boyd, 2007;Lukas et al, 2005). Consequently, while leader-follower relationships can occur among non-relatives, many (van Vugt, 2008;Schoof et al, 2009;Wikberg, 2012;Nichols et al, 2012;Yano, 2008;Berg et al, 2009;Mumme et al, 1988;Lewis et al, 2011;Andersson and Wallander, 2004;Hoppitt et al, 2008) (if not most) observed leader-follower behaviour has occurred between relatives. Therefore the general conclusions drawn from our model should still be applicable to a wide variety of animal species.…”
Section: Limitations and Future Directionsmentioning
confidence: 93%
“…Despite this, little is known theoretically about the evolution of dispersal involving leader-follower relationships. It is standard in mathematical models to assume that dispersal occurs independently, but in many species dispersal occurs in groups of individuals that are often but not always related, and group dispersal is frequently initiated by a subset of individuals (Schoof et al, 2009;Wikberg, 2012;Nichols et al, 2012;Yano, 2008;Berg et al, 2009;Mumme et al, 1988;Lewis et al, 2011;Andersson and Wallander, 2004). The few models that incorporate the concept of group dispersal do not examine the emergence or maintenance of this biological phenomenon, nor do they assume the presence of leader-follower relationships (Gardner and West, 2006;Gardner et al, 2009;Nakamaru et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…According to the breeding system hypothesis (Greenwood, 1980), cooperatively breeding birds with biparental care, a socially monogamous and a resource defense mating system should have female-biased dispersal pattern. Several cooperatively breeding birds are yet known to have the malebiased dispersal patterns, such as Brown jays (Cyanocorax morio) (Williams, 2000;Williams and Rabenold, 2005), Seychelles warblers (Acrocephalus sechellensis) (Richardson et al, 2002) and White-throated magpie-jays (Calocitta formosa) (Berg et al, 2009). Interestingly, a close relative to the Black-throated tits, the cooperatively breeding longtailed tits (Aegithalos caudatus) exhibit female dispersal (Sharp et al, 2011).…”
Section: Male-mediated Gene Flow Has Resulted In Cytonuclear Discordancementioning
confidence: 99%